ANATOMICAL EVIDENCE FOR REINSTATING SCHIZOSTACHYUM LONGISPICULATUM AND S. BIFLORUM - SUHARDJONO PRAWIROATMODJO (REINWARDTIA, 1982)
Based on the differences in their leaf anatomy, it is suggested that S. longispiculatwm, S. biflorum and S. blumei, should be considered as three distinct species.